Corrosion Behavior of Steel 37 under Dynamic Conditions in 0.1 N H2SO4 - Alaa Abdulhasan Atiyah; Dhuha Albusalih (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
An aggressive environment has a substantial effect on the progression of corrosion on metal surfaces and alloys. This study investigated the effect of one of the parameters that affect the corrosion process, the stirring rate, on the behavior of Steel 37 in 0.1 N of sulfuric acid. The main method used in this study is an electrochemical method (using a potentiostat at a scan rate of 3 MV.sec-1), applied at three different temperatures (25, 30, and ˚C). To evaluate the parameters of corrosion in this study, the Tafel extrapolation method was used. At a constant stirring rate, the corrosion current density was found to be increased with increasing temperature at a constant stirring rate. In addition, the corrosion rate increased with increasing stirring rate at a constant temperature due to the rise of the diffusion coefficient of oxygen. The Levich equation was used to calculate the limiting current densities, as well as the mass transfer coefficient (Km) and the Sherwood number (Sh). The Km values were calculated and it was found that the mass transfer coefficient was greater at higher temperatures and stirring rates. The results also revealed that the smallest values of Sh (2.575, 3.897) occurred at 30 °C at two stirring rates (200 and 400 rpm).